دور الرقمنة في تحقيق رضا العملاء - عيش عبد النور (My University, 2024)
This study aimed to determine the role of digitization through its dimensions (material, administrative, human, and security) in achieving customer satisfaction at Algeria Telecom Corporation in M’Sila and to clarify the relationship between the independent and dependent variables. The questionnaire was relied upon to collect data and it was distributed to a random sample of 50 customers. We relied on the descriptive approach to collect and analyze information. The statistical analysis program SPSS was used to test the hypotheses We concluded that digitization has a role in achieving customer satisfaction and gaining their loyalty, by improving the quality of services provided to them.
Keywords: : digitization; physical dimension; administrative dimension; human dimension; security dimension; customer satisfaction.